Penyuluhan tentang Gempa Bumi dengan Media Leaflet pada Masyarakat di Kelurahan Malabero Kota Bengkulu - Dwi Putri Sulistiya Ningsih; Ida Rahmawati; Rina Aprianti; Susilo wulan; Vike Pebri Giena; Yulita Elvira (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: An earthquake is a natural calamity that cannot be avoided, occurs unexpectedly, and cannot be correctly estimated at its epicenter. Earthquakes can be predicted in the range of times that allow them to occur, but not their exact moment of occurrence or strength. Counseling is carried out to prepare the community to be able to deal with earthquake disasters when they occur. Purpose: To improve community preparation in the event of an earthquake disaster. Methods: Community service activities include employing leaflet media to provide earthquake catastrophe advice. People residing in earthquake-prone areas, such as Malabero Village and Bengkulu City, were targeted for the exercise. Results: Before and after receiving earthquake disaster preparedness counseling, there is an improvement in community understanding. Conclusion: By delivering health education using leaflets as a medium for health promotion, the public's understanding of readiness in coping with seismic disasters can be increased.